Sequence and phylogeny of the complete mitochondrial genome of the Himalayan jungle crow (Corvidae: Corvus macrorhynchos intermedius) from Pakistan. Issue 1 (2nd January 2020) - Iqbal, Farheena; Ayub, Qasim; Song, Beng Kah; Wilson, Robyn; Fahim, Muhammad; Rahman, Sadequr
Abstract: Corvus macrorhynchos formerly referred to as the jungle crow or the large-billed crow is a polytypic species with unresolved taxonomy, comprising various subspecies widespread across South, Southeast, and East Asia. In this study, we report the complete mitogenome of one of these subspecies, Corvus macrorhynchos intermedius (Himalaya crow), from Pakistan. The mitochondrial genome is circular, 16, 927 bp and contains typical animal mitochondrial genes (13 protein-coding genes, 2 ribosomal RNA, and 22 transfer RNA) and one non-coding region (D-loop) with a nucleotide content of A (30.6%), T (24.8%), G (14.8%), and C (29.8%). Phylogenetic analysis using the whole mitochondrial genome showed that C. m. intermedius and only reported subspecies Corvus macrorhynchos culminatus (Indian Jungle crow) are genetically distinct and it supports the recognition of the latter as a separate biospecies.